Ginger Extract as an Antimicrobial Agent: A Case Study in Chicken Meat† - S., Sudharshan.; M.N., Fairoze.; R., Prabha.; D., Rathnamma.; C., Renuka Prasad. (Journal of Meat Science, 2011)
The extracts of many spices and herbs have become popular in food industry in the recent years for their antimicrobial and antioxidant properties. Ginger (Zingiber officinale roscae) of family Zingiberaceae is a commonly used spice in India. This study was conducted to examine the antimicrobial efficacy of ginger on few meat borne pathogens in fresh chicken. Staphylococcus aureus was most sensitive to ginger oil extract followed by Salmonella typhimurium, Escherichia coli O157, Bacillus cereus, Bacillus subtilis and Klebsiella pneumoniae. Aqueous extract of ginger had no effect on bacterial counts whereas oil extract of ginger decreased bacterial counts significantly (P
Keywords: Ginger; antimicrobial effect; chicken meat; food borne pathogens